Antioxidant enzymes in blood of patients with Friedreich's ataxia. Issue 5 (1st May 2002) - Tozzi, G; Nuccetelli, M; Lo Bello, M; Bernardini, S; Bellincampi, L; Ballerini, S; Gaeta, L M; Casali, C; Pastore, A; Federici, G; Bertini, E; Piemonte, F
Abstract : Background and Aims: Increased generation of reactive oxygen species and mitochondrial dysfunction may underlie the pathophysiology of Friedreich's ataxia, the most common inherited ataxia, due to GAA expansion in a gene coding for a mitochondrial protein (frataxin), implicated in the regulation of iron metabolism. Because iron overload would cause oxidative stress in Friedreich's ataxia, we investigated the enzyme antioxidant system in the blood of 14 patients by determining superoxide dismutase, glutathione peroxidase, and glutathione trasferase catalytic activities. We also studied the glutathione S-transferase genotype polymorphism in order to evaluate its possible influence on enzyme activity. Methods: Blood samples were obtained from 14 unrelated patients with Friedreich's ataxia and 21 age matched healthy subjects. Antioxidant enzyme determinations were spectrophotometrically assayed using specific substrates; the glutathione S-transferase genotype polymorphism was analysed by endonuclease restriction mapping of exon 5 and 6 amplification products. Results: There was a significant elevation of the superoxide dismutase/glutathione peroxidase activity ratio (0.037 (0.01) v 0.025 (0.008) of controls) and an 83% rise of glutathione transferase specific activity (0.22 (0.1) v 0.12 (0.03) nmol/min/mg protein) in blood of patients with Friedreich's ataxia than in the controls. The genotype polymorphism of glutathione S-transferase enzyme did not show any relevant differences when compared to that of healthy subjects. Conclusions: Data show an impairment in vivo of antioxidant enzymes in patients with Friedreich's ataxia and provide evidence of an increased sensitivity to oxidative stress, supporting a consistent role of free radical cytotoxicity in the pathophysiology of the disease.